Book Review: “Understanding New Media”, 2nd Edition (2018) by Eugenia Siapera - Ibrahim, Adamkolo Mohammed; Pate, Umaru A. (UI Scholars Hub, 2019)
With the first edition of this work conceived well over a decade ago and the present edition published just about a year ago, there is still much to understand about technologies and new media intellectually and empirically. Dr Eugenia Siapera’s work “Understanding New Media”, 6th Edition eases the task for readers by providing comprehensive and readable information about much that we need to know on the concept ‘new media’, its variants and their relationships with the social and other non-social elements of society. Diversity, hegemony, production, consumption, theories and political economy are some of the key themes Dr. Siapera examined critically in her work. Because of the importance she attaches to the issue of political economy, the author dedicated a whole chapter (Chapter 2) to political economy of new media. Using critical discourse analysis approach, we reviewed chapters 1, 2 and 5 only. This is because of the critical importance of the analysis provided in these chapters on some of the most intriguing topics in media studies and research such as issues surrounding the concept of new media, the influence of political economy on media content dissemination and consumption as well as the negative uses and effects of new media in society, especially on young users.